2019
DOI: 10.1002/ncp.10256
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Enteral Protein Intake in Critically Ill Trauma and Surgical Patients

Abstract: Background Published guidelines recommend providing at least 2 g/kg/d of protein for critically ill surgical patients. It may be difficult to achieve this level of intake using standard enteral formulas, thus necessitating protein or amino acid supplementation. Herein, we report our approach to enteral protein supplementation and its relationship with urinary nitrogen excretion and serum transthyretin concentrations. Methods This was a retrospective cohort study in which we reviewed critically ill trauma and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…It is necessary for nutritional support to maintain adequate metabolic pathways without causing redistributions that compromise the functionality and structure of the organs. The importance of protein intake has been observed in EL patients, resulting in reduction in infectious complications, hospital stay, morbidity associated with energy excess, and in turn reduced mortality in cases of sepsis [ 25 ].…”
Section: Impact Of Disease and Treatments On Nutritional Status At Th...mentioning
confidence: 99%
“…It is necessary for nutritional support to maintain adequate metabolic pathways without causing redistributions that compromise the functionality and structure of the organs. The importance of protein intake has been observed in EL patients, resulting in reduction in infectious complications, hospital stay, morbidity associated with energy excess, and in turn reduced mortality in cases of sepsis [ 25 ].…”
Section: Impact Of Disease and Treatments On Nutritional Status At Th...mentioning
confidence: 99%
“…7 Many studies have shown improved outcomes with early highprotein diet (up to 2 g/kg per day). [63][64][65][66][67][68] Obese patients should be given special nutritional considerations. Obesity is a risk factor for severe ARDS in the setting of bacterial or viral infections, ischemic heart disease, and complicated post-cardiotomy shock.…”
Section: Indirect Calorimetrymentioning
confidence: 99%
“…Current ESPEN guidelines recommend a 1.3 g/kg/day protein intake combined with an exercise program 7 . Many studies have shown improved outcomes with early high‐protein diet (up to 2 g/kg per day) 63–68 …”
Section: Introductionmentioning
confidence: 99%
“…Yet, although a significant increase of protein intake was achieved by using this protocol, not all their patients received optimal protein intake (> 80%) of the aimed target, which pose the question why the investigators did not consider the use of protein supplements. In a recent study, O’Keefe et al demonstrated that the combined use of empiric EN protein supplement is safe, when used in combination with EN in critically ill patients, and reaches 2 g/kg/day of protein intake per day [9]. In fact, enteral protein supplementation is one of a number of possible ways which has previously been demonstrated to increase protein intake in critically ill patients [8].…”
mentioning
confidence: 99%